KAJIAN PERUBAHAN GARIS PANTAI PROVINSI SUMATERA BARAT PERIODE 2003 – 2016 - Haryani Haryani; Agus Irianto; Nurhasan Syah (TATALOKA, 2019)
In the Law No. 24/2007, that actions that can be taken on disaster management include prevention, mitigation, preparedness and emergency response. One of the actions that can be done pre-disaster (mitigation) is the need to know the characteristics of disaster as one of the mitigation efforts. West Sumatera province has 19 cities and regencies where 6 of them often experience abrasion and accretion disaster because it is a coastal area directly adjacent to the Indian Ocean. This study aims to examine the characteristics of abrasion and accretion disasters along the coast of West Sumatra Province from 2003 to 2016. By knowing the characteristics of abrasion and accretion from 2003 and 2016 it will be known which beaches are experiencing abrasion or accretion. This research is qualitative and quantitative descriptive research with Geographic Information System (GIS) analysis method to get characteristic of abrasion and accretion disaster in coastal area of West Sumatra. there has been a disaster of abrasion and accretion in 32 points spread across 6 districts and cities, namely West Pasaman District, Agam Regency, Padang Pariaman District, Pariaman City, Padang City and Padang Pariaman District. , an abrasion disaster in the coastal area of West Sumatra Province of 732.69 Ha and 55.4 ha of acres. This proves that the abrasion debacle causes the decrease of land in West Sumatera Province which is big enough that is average 56,3 Ha / year, while the addition of land is only 4,26 Ha / year. The farthest abrasion disasters are located in South Pesisir Regency, which is 45.70 m or 3.52 m / year on average. While the farthest accretion is in the South Pesisir Regency is as far as 36.91 or an average of 2.84 m / year.